Estremo d’ombra: an interactive electronic composition - Morciano, Lara (Musica/Tecnologia, 2018)
In Estremo d’ombra, for five soloists and electronics (2015), an interactive system was developed in order to enable the synchronisation between the performers and the live electronics – consisting of real-time processing and synthesis – to be composed in detail. This system led to the creation of a ‘centralised’ score for the electronics realised in the Antescofo programming language, which pilots electroacoustic processes executed in the SuperCollider and Max/MSP environments and displays scores for the performers in openFrameworks. The Antescofo system allows for the expression of temporally complex interactions involving the instrumentalists, rendering the composition of the real-time electronics more dynamic and expressive. This system eliminated the need for a conductor or a pedal of activation, thereby allowing the performers to interact and move more freely. The staging of the work is emphasised by lighting and a symbolic dramatic narrative.